Kebijakan dan Isu Kesehatan dalam Konteks Otonomi Daerah - Andri Kurniawan (Universitas Syiah Kuala, 2010)
ABSTRACT: Increased attention to the problem of efficiency and equity in the provision of medical equipment and limited people's choice to make health care reform the health sector become an important agenda in many countries. Although health policy implications into the discourse of prominent intensity in the academic literature, however, health policy implications are not commonly found in developing countries. It is difficult because of the exchange balance (trade off) between on the one hand the efficiency and equity on the other side. Decentralization became a kind of necessity, the sine qua non, in connection with the idea of democratization in the administration of state power. Decentralization is one of the pillars of constitutionalism is the idea of power sharing in a vertical / spatial, but on the other hand, decentralization / autonomy turns out to complicate the implementation of the functions and duties of government in general and specifically in health problems (if not based on an institutional Virtue) for the government and the regions. Policy and Health Issues in the Context of Regional Autonomy